Contribution to ethnobotanical knowledge of the chile water (Capsicum annuum L.) in the Central Valleys of Oaxaca, Mexico - Montaño-Lugo, María Lesly; Velasco Velasco, Vicente Arturo; Ruíz Luna, Judith; Campos Ángeles, Gisela Virginia; Rodríguez Ortiz, Gerardo; Martínez Martínez, Leonardo (Revista Mexicana de Ciencias Agrícolas, 2018)
Zapotec peoples of the Central Valleys of Oaxaca, Mexico, represent the core of one of the most important cultures of the state, despite the structural changes, have shown a great ability to rebuild and reaffirm their identity from their practices and skills Traditional. In order to document the ethno-ecological knowledge of the chile water (Capsicum annuum L.), the present study was conducted in eight locations in the region in 2010. Non-probability sampling (discretionary and snowball) and the ethnographic method was used. The results were grouped into the complex: kosmos, corpus and praxis, for which interviews with producers and consumers of water were made chili. 45% edible, medicinal 36%, 9% ritual amulet 6% and 4% ornamental: five uses ranging significance by use were found. It was observed that the producers interviewed have extensive knowledge about the medicinal, ritual and charm, while consumers interviewed have it in the edible and medicinal use. The inhabitants of the communities of the Central Valley region have broad ethno-ecological knowledge, however, the study of traditional ethnobotanical relationships based on empirical knowledge of ethnic groups, is still incipient in regards to endemic flora localities of the Zapotec culture.